La possessione nella pantomima - Manlio Marinelli (Danza e Ricerca)
The paper aims to explore the relationship between pantomime and possession (enthousiasmos) in particular in the imperial age. The author examines various sources in this regard: the treatise De Saltatione by Lucian of Samosata, excerpts from Dion of Prusa and Plutarch, and some epigrams from the Palatine Anthology. From the sources, it is possible to highlight that during the performance the spectators and pantomimes shared a state of mania: Dion and Plutarch state that this particular condition had a bad influence on the psychological balance of the performer and the audience, while Lucian proposes two different categories of pantomime: the best is able to manage the state of mania, in contrast to the second that loses his abilities as well as control of himself.